2009
DOI: 10.1007/s00429-009-0210-z
|View full text |Cite
|
Sign up to set email alerts
|

Paracingulate asymmetry in anterior and midcingulate cortex: sex differences and the effect of measurement technique

Abstract: Many structural brain asymmetries accompany left hemisphere language dominance. For example, the cingulate sulcus is larger in the medial cortex of the right hemisphere, while the more dorsal paracingulate sulcus is larger on the left. The functional significance of these asymmetries is unknown because fMRI studies rarely attempt to localize activation to specific sulci, possibly due to difficulties in consistent sulcal identification. In medial cortex, for example, there are many regions of partial sulcal ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 73 publications
(112 reference statements)
3
36
1
Order By: Relevance
“…17 Sex was also added a priori as a potential confounding factor, as some studies have reported sex-related differences in ACC asymmetry. [25][26][27] To control for the potential bias effect of psychotic symptoms, we performed our statistical analyses using the total PANSS score as a confounding covariate.…”
Section: Discussionmentioning
confidence: 99%
“…17 Sex was also added a priori as a potential confounding factor, as some studies have reported sex-related differences in ACC asymmetry. [25][26][27] To control for the potential bias effect of psychotic symptoms, we performed our statistical analyses using the total PANSS score as a confounding covariate.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, it is not yet entirely clear whether a more precise definition of the PCS can be achieved by including or excluding fragmented sulci running parallel to the CS (e.g., Leonard et al 2009). Nevertheless, it has already been shown that variations in midcingulate fissurization are indeed associated with differences in performance at both the behavioral (e.g., Fornito et al 2004) and the electrophysiological level (Huster et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that a leftward-asymmetric doubling of gyri in the midcingulate region (see, e.g., Vogt et al 1995) is more pronounced in males than females (Huster et al 2007;Paus et al 1996;Yücel et al 2001; but see Leonard et al 2009, for a recent contradictory finding). This suggests a stronger degree of lateralization in men.…”
Section: Introductionmentioning
confidence: 99%
“…The sulcal pattern of ACC was visually assessed using 3-D, mesh-based reconstruction of cortical folds to measure the occurrence and extent of local sulci (e.g., Leonard, Towler, Welcome, & Chiarello, 2009;Huster, Westerhausen, Kreuder, Schweiger, & Wittling, 2007;Fornito et al, 2004;Yucel et al, 2001). ACC sulcal pattern was classified as "single" or "double parallel" type (Ono et al, 1990) based on the presence or absence of a PCS (Figure 2).…”
Section: Acc Classificationmentioning
confidence: 99%
“…The PCS was considered absent if there were no clearly developed horizontal sulcus elements parallel to the cingulate sulcus and extending at least 20 mm (interruptions or gaps in the PCS course was not taken into account for the length measure). The finer distinction between "present" and "prominent" PCS ( Yucel et al, 2001;Paus et al, 1996), leading to three ACC sulcal pattern types, was not used here because this distinction is based on the PCS length of adult brains-that is, greater than 20 mm according to Pausʼs classification (Paus et al, 1996) or greater than 40 mm according to Yucelʼs classification (Yucel et al, 2001) for a prominent PCS (Leonard et al, 2009). Furthermore, the classification of ACC morphology into five categories by grouping the individual measurements of PCS in 15-mm steps was also proposed (Huster et al, 2007).…”
Section: Acc Classificationmentioning
confidence: 99%